1985
DOI: 10.1093/ajcn/42.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal bone density and milk consumption in childhood and adolescence

Abstract: Skeletal mass is a major determinant of susceptibility to osteoporotic fracture in menopause. At menopause, the skeletal mass is the resultant of the Peak Skeletal Mass (PSM) reached early adulthood minus the bone mass lost through the process of Adult Bone Loss (ABL). Current interventions for the maintenance of skeletal resilience in advanced age address the ABL peri- or postmenopausally. This study indicates that the effects of milk consumption in childhood and adolescence on bone density may manifest as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1
7

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(104 citation statements)
references
References 3 publications
8
88
1
7
Order By: Relevance
“…[3][4][5][6] Several researchers have reported differences in perceived or ideal body size in adolescent and college-aged AfricanAmerican and White females.5'7'8 Adult African-American women have also been shown to be less likely to think that being overweight is a problem9 or to perceive themselves as overweight.10 National data on the prevalence of weight loss attempts indicate that dieting patterns are similar among overweight African-American and White adult women and that, among women who are not overweight, dieting is less common in African Americans than in Whites. [10][11][12][13][14] The …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Several researchers have reported differences in perceived or ideal body size in adolescent and college-aged AfricanAmerican and White females.5'7'8 Adult African-American women have also been shown to be less likely to think that being overweight is a problem9 or to perceive themselves as overweight.10 National data on the prevalence of weight loss attempts indicate that dieting patterns are similar among overweight African-American and White adult women and that, among women who are not overweight, dieting is less common in African Americans than in Whites. [10][11][12][13][14] The …”
Section: Introductionmentioning
confidence: 99%
“…Murphy et al (22) found a higher BMD in females aged 40-49y who had had a higher milk intake until the age of 20y. There was a similar study on the association between BMD and the previous milk ingestion habits of post-menopausal females (23). The presence or absence of milk ingestion habits during childhood and youth was associated with the maintenance of a high level BMD at and after middle age, and the present Ca intake was higher in those subjects with a previous milk ingestion habit.…”
Section: Discussionmentioning
confidence: 72%
“…[39] Adequate calcium intake is necessary to maximize peak bone mass and minimize both the risk of fractures in adolescence and the development of osteoporosis in adulthood. [40] The recommended calcium intake in children between the ages of three and eight is 800 mg/day, while it is 1300 mg/d for older children and adolescents between the ages of 9 and 17. [41] The Turkish population must be informed about the importance of adequate lifelong calcium intake for bone health.…”
Section: Discussionmentioning
confidence: 99%